Optimizing data linkage for maximizing the potential of Luxembourg’s national cancer registry: a comprehensive scoping review - Lima, Bruno; Hasan, Farah; Kannan, Pragathy; Schnell, Michael; Mafra, Allini; Couffignal, Sophie; Backes, Claudine (Frontiers in Oncology, 2025)
Population-based cancer registries (PBCRs) provide international standardized indicators and evaluate public health actions and cancer care. Their research potential can be significantly enhanced through linkage with secondary data sources, such as biobanks, sociodemographic or genomic data. However, legal, ethical, and technical challenges often hinder such integration. This scoping review aims at identifying data linkage opportunities between cancer registries and secondary data sources, while describing the current state of the Luxembourg’s National Cancer Registry (RNC). Ultimately, steps for linkages between cancer registries and biobanks and/or sociodemographic data are assessed to enhance cancer research and public health initiatives. A scoping review using PubMed and Embase databases was performed. English guidelines, reports, and qualitative and quantitative studies on hospital-based cancer registries, PBCRs, and site-specific registries were included. One thousand three hundred and twelve articles (n = 1312) were identified. After scanning titles and abstracts, 49 articles were examined for full-text reading, where fifteen articles met the inclusion criteria. Moreover, 13 articles were included following the snowball search approach (n = 28). Included articles report significant differences between countries in all avenues, including data availability and harmonization, confidentiality, access to data, exchange, and linkage methods. Results underline that PBCR’s potential, efficiency, and cost-effectiveness are maximized thanks to linkage activities with secondary data sources such as biobanks or sociodemographic databases. In addition, the results of this scoping review enable the identification of key questions to address before establishing data linkage grouped into five domains being: (i) legal permission, (ii) data availability assessment, (iii) data flow protocol, (iv) linkage key and (v) linkage method. In conclusion, addressing the five key domains identified in this review will support the development of robust, efficient, and ethically sound data linkage strategies, unlocking the full research potential of PBCRs and to aid decision making.